Serious fun : how guided play extends children's learning - Masterson, Marie L.; Bohart, Holly (National Association for the Education of Young Children, 2019)
A practical book for teachers consisting of 10 YC and TYC articles on the importance of integrating rich content-based, teacher-guided instruction with meaningful child-centered play to nurture children's emerging capabilities and skills. The emphasis is on teachers' active, intentional role in children's play to guide learning. Two sections: four general articles that discuss the topic, followed by six content-area articles on math, literacy, drama, art, STEM, and outdoor learning. Marie wrote the introduction as well as other material. Note: This book will not be part of the Spotlight series.